Pengukuran Kinerja Keuangan Berbasis Economic Value Added Pada Perusahaan Sektor Makanan dan Minuman: Measurement of Financial Performance Based on Economic Value Added in Food and Beverage Companies - Clara Neltje Meini Rotinsulu; Taufik Bidullah; Sri Rahayu Husen (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2025)
This study aims to measure the financial performance of food and beverage companies based on the Economic Value Added (EVA) approach from an internal management perspective. A descriptive quantitative method is employed using secondary data derived from companies’ financial statements obtained from the Indonesia Stock Exchange and official corporate websites. The analysis utilizes operating profit, tax expense, capital structure, and cost of capital components to calculate Net Operating Profit After Tax, Weighted Average Cost of Capital, and EVA. The results indicate that food and beverage companies are able to generate positive EVA values, although fluctuations are observed. These fluctuations suggest that economic value creation is influenced by operational performance dynamics and capital efficiency. The findings provide managerial implications for evaluating financial performance and supporting value-oriented decision making.